A bust but no boom: responses of floodplain bird assemblages during and after prolonged drought. (4th September 2015) - Selwood, Katherine E.; Clarke, Rohan H.; Cunningham, Shaun C.; Lada, Hania; McGeoch, Melodie A.; Mac Nally, Ralph; Phillimore, Albert
Summary Climate change alters the frequency and severity of extreme events, such as drought. Such events will be increasingly important in shaping communities as climate change intensifies. The ability of species to withstand extreme events (resistance) and to recover once adverse conditions abate (resilience) will determine their persistence. We estimated the resistance and resilience of bird species during and after a 13‐year drought (the 'Big Dry') in floodplain forests in south‐eastern Australia. We conducted bird surveys at the beginning and end of the Big Dry, and after the abrupt end to the drought (the 'Big Wet'), to evaluate species‐specific changes in reporting rates among the three periods. We assessed changes in bird‐breeding activity before and after the Big Wet to estimate demographic resilience based on breeding. Between the start and the end of the Big Dry (1998 vs. 2009), 37 of 67 species declined substantially. Of those, only two had increased reporting rates after the Big Wet (2009 vs. 2013) that were equal to or larger than their declines, while three partially recovered. All other declining species showed low resilience: 25 showed no change in reporting rates and seven declined further. The number of breeding species and total breeding activity of all species declined after the Big Wet, and there was no change in the number of young produced. The Big Dry caused widespread declines in the floodplain avifauna. Despite the drought being broken by 2 years of well‐above‐average rainfall and subsequent near‐average rainfall, most species showed low resilience and there was little indication that overall breeding had increased. The effects of drought appeared to be pervasive for much of the floodplain avifauna, regardless of species traits (species body mass, fecundity, mobility or diet). Ecosystems such as these are likely to require active management and restoration, including reinstatement of natural flooding regimes, to improve ecological condition, to enhance resistance and resilience to extreme climate events.